A governança na gestão das Unidades de Conservação da Amazônia : o SNUC em questão - Ferreira, Hueliton da Silveira (2021)
he present research addresses the public policies for the creation and management of Conservation Units (CU´s), regulated by Law 9.985/2000, through which the National System of Conservation Units (in Portuguese, SNUC-Sistema Nacional de Unidades de Conservação) was established at Union, State and Municipality levels. According to the Ministry of Environment, there are more than 800 units in total in the two regions, 56.5% of which are under federal administration, 40% under state administration and only 3.5% under municipal administration, covering 15% of the country's continental area and 26% of the marine area under special protection. The management models currently used in specific organs are analyzed, as well as the structure and the organizational, political-administrative and institutional system adopted, which are reflected on the dynamics of territorial management practiced in the 824 Conservation Units of various categories, magnitudes and typology of natural and socio-environmental areas in Brazil´s Legal Amazon. Differences in the institutional and political arrangements, which are deployed and operated in the Conservation Units, were identified and classified, with the purpose of critically characterizing and confronting each management model adopted and the infrastructural and superstructural apparatus at different levels of environmental and governance territorial. The research starts from a hypothesis that focuses on the socio-spatial mechanisms and dynamics that generate differentiation in the territorial organization, according to the environmental management models practiced by the State in its spheres of government, and an incipient participation of the municipal sphere in the national CU´s system, within the political arrangement institutional decentralization of environmental policies. The procedures used in the present research were based on specific bibliography, internal documents and published papers, on primary field data collection, through sampling of the study universe, on statistical and cartographic secondary data. The theoretical support made use of the ontology of geographic space as a system of objects and a system of actions in a hybrid geographic space, according to the framework presented by Milton Santos (1977), who applies the concept of dialectical and socio-spatial formation, elaborating a theory which state that a society becomes concrete through the space that it produces in terms of structure, process, function and form. An approach about the concepts of territory and territoriality was included, which configure conservation units as specially protected territorial spaces. Philosophical anchorage in Foucault was sought, according to studies developed in the 1990s, referring to the concept of governmentality, which is a theoretical tool that, according to the author, translates a set of institutions, procedures, analyses, reflections, calculations and tactics that allow to exercise a specific and complex form of power that is government. Throughout the work, the theoretical-conceptual and methodological basis was built, the specific delineation of the object proposed for study, and postulated, based on structured hypotheses, the thesis that currently Brazil does not practice a national system as proposed by SNUC, but a system at the federal level that can be called “SIFUC”. Based on this thesis, the feasibility of adjusting state and municipal systems compatible with the SNUC is exposed, fostering its creation in states and municipalities where they do not yet exist, in articulation with the governance of the territory at different scales of inter-institutional planning and intersectoral, democratically and efficiently. In conclusion, there is a need for a national system of protected areas that, based on governance, promotes articulation with its set of CU´s and with other protected areas, with a view to achieving the effective protection of biodiversity, ecosystem services and the way of life of the residents of these Units and their areas of influence.